Determinants of Loyalty among Gen Z and Millennial Muslim Tourists in Jabodetabek toward Leading Halal Tourism Destinations in Indonesia - Andryana, Andryana andri; Zaerofi, Afif; Indra, Indra (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to analyze the determinants of loyalty of Millennial and Gen Z Muslim tourists in Greater Jakarta (Jabodetabek) to leading halal tourism destinations in Indonesia. The primary focus is on the influence of destination image (affective and cognitive) on halal experiences, satisfaction, and tourist loyalty. Drawing on Expectation Confirmation Theory (ECT) and Muslim consumer behavior theory, this study seeks to address the research gap regarding how urban Muslim tourists evaluate halal experiences at destinations in Muslim-majority and minority regions that are considered high-priority tourism destinations in Indonesia. The research method used was a quantitative approach with Partial Least Squares Structural Equation Modeling (PLS-SEM). Primary data were obtained through an online questionnaire distributed to 137 Muslim Millennials and Gen Z respondents residing in Greater Jakarta (Jabodetabek) and having visited leading halal tourism destinations. The research instrument measured affective image, cognitive image, halal experience, satisfaction, and tourist loyalty using a five-point Likert scale. The results showed that affective image and cognitive image had a significant positive effect on halal experience and tourist loyalty. Halal experience was shown to have a very strong positive effect on tourist satisfaction, while tourist satisfaction did not have a significant direct effect on loyalty. These findings confirm that loyalty in the Millennial and Gen Z segments is shaped more by perceptions of destination image and halal experience than by satisfaction alone. Practically, this research provides important implications for halal destination managers to strengthen the emotional and rational aspects of providing Sharia-compliant halal services while building deep emotional bonds with young Muslim tourists.